EVALUATION OF REGIONAL EFFICIENCY DISPARITIES BY EFFICIENT FRONTIER ANALYSIS - Dzemydaitė, Giedrė; Galinienė, Birutė (Ekonomika, 2013)
Abstract. The nonparametric methods, such as data envelopment analysis, free disposal hull and order-α frontier analysis, have been applied in this study to evaluate the efficient frontier which extends the application of the production function of regions. These mathematical programming methods allow evaluating the effectiveness of the regional spatial aspects. In recent studies, efficient frontier methods are applied to evaluate regional policy issues of the European Union. The purpose of this article is to present a more detailed evaluation of regional disparities by analysing regional infrastructure, human capital efficiency, and linkages among the regions. The application of frontier methods reveals their feasibility for studying regional inputs and outputs to asses a more detailed and more reasonable allocation of funds among Lithuanian regions. A more detailed territorial breakdown is selected in this paper to identify a wider scale of efficiency differences among the regions. From the practical point of view and according to the results, more balanced planning tools are suggested for fund allocation decisions in Lithuanian regions while planning infrastructure and human capital development. As efficient regions are identified, it is recommended to invest in more indirect factors to enhance regional growth. while in inefficient regions more emphasis should be made on more direct interventions to foster economic activity because current investments give insufficient returns. The present type of research is a case study. Key words: regional disparities, regional efficiency, economic development, spatial data envelopment analysis, nonparametric analysis